2013
DOI: 10.1186/1475-2840-12-57
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disturbances and worsening of atherosclerotic lesions in ApoE-/- mice after cola beverages drinking

Abstract: BackgroundAtherosclerosis is a major health burden. Metabolic disorders had been associated with large consumption of soft drinks. The rising incidence of atherosclerosis and metabolic alterations warrants the study of long-term soft drink consumption’ effects on metabolism and atherosclerosis in genetic deficiency of apolipoprotein E which typically develops spontaneous atherosclerosis and metabolic alterations.MethodsApoE-/- mice were randomized in 3 groups accordingly with free access to: water (W), regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 30 publications
4
27
2
Order By: Relevance
“…27 In addition to weight gain, both saccharin and aspartame have been associated with impaired glucose homeostasis in mice, 24,28,29 and aspartame was also shown to induce hyperinsulinemia, 25 impaired insulin tolerance 24,28 and worsened atherosclerosis in genetically-susceptible (ApoE ¡/¡ ) mice. 30,31 In contrast, Flatt and colleagues described anti-hyperglycemic and antihyperinsulinemic effects for saccharin in genetically obese (ob/ob) mice, coupled with attenuation of weight gain. 32 In fact, beneficial effects of NAS were at times described to co-occur with detrimental ones in some studies.…”
Section: Introductionmentioning
confidence: 99%
“…27 In addition to weight gain, both saccharin and aspartame have been associated with impaired glucose homeostasis in mice, 24,28,29 and aspartame was also shown to induce hyperinsulinemia, 25 impaired insulin tolerance 24,28 and worsened atherosclerosis in genetically-susceptible (ApoE ¡/¡ ) mice. 30,31 In contrast, Flatt and colleagues described anti-hyperglycemic and antihyperinsulinemic effects for saccharin in genetically obese (ob/ob) mice, coupled with attenuation of weight gain. 32 In fact, beneficial effects of NAS were at times described to co-occur with detrimental ones in some studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we reported paradoxical worsening of atherosclerosisat the end of cola beveragesdrinking-treatment [10]. However interpretation of these findings could be questioned considering that determinations had been performed at a single time point immediately after drinking-treatment cessation and the recovery period might have been insufficient to observereversal of damage if any.…”
Section: Discussionmentioning
confidence: 93%
“…Hypertension, hyperglycemia, increased body weight, dyslipidemia and echocardiographic alterations were observed while pathology findings were scarce, related to aging rather than treatment [8], [9]. Recently we observed that ApoE −/− C57BL/6J mice exhibited a particular sensitivity to the effects of cola beverage drinking [10]. Arterial pathology was induced bysucrose-sweetened cola (C) drinking in association with hyperglycemia [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In atherosclerotic apolipoprotein E-deficient (apoE-/-) mice, consumption of aspartame-acesulfame K sweetened 'light' cola was found to accelerate the progression of atherosclerotic plaques and the accumulation of sub-endothelial lipid-laden macrophages [27,28]. Also, in vitro treatment of apoA-I or HDL with physiological concentrations of aspartame, acesulfame K, or saccharin resulted in their pro-oxidative and pro-atherogenic modifications [29,30].…”
Section: Introductionmentioning
confidence: 99%